To solve for the variable x, we can first combine like terms on the right side of the equation:
10x + 2x = 6y
Combining like terms, we have:
12x = 6y
Now, we can isolate x by dividing both sides of the equation by 12:
(12x)/12 = (6y)/12
Simplifying, we get:
x = (6/12)y = (1/2)y
Therefore, the correct answer is:
A. x = 1/2y
Given the equation below solve for the variable x .
10x = 6y - 2x
A. x = 1/2y
B. x = 4/3y
C. x = 2y
D. x = 3/4y
3 answers
U sure?
Apologies for the confusion earlier. Let's solve the equation correctly:
10x = 6y - 2x
To isolate the variable x, we can add 2x to both sides:
10x + 2x = 6y - 2x + 2x
This simplifies to:
12x = 6y
Now, divide both sides of the equation by 12 to solve for x:
(12x)/12 = (6y)/12
Simplifying further, we get:
x = (1/2)y
Therefore, the correct answer is:
A. x = 1/2y
10x = 6y - 2x
To isolate the variable x, we can add 2x to both sides:
10x + 2x = 6y - 2x + 2x
This simplifies to:
12x = 6y
Now, divide both sides of the equation by 12 to solve for x:
(12x)/12 = (6y)/12
Simplifying further, we get:
x = (1/2)y
Therefore, the correct answer is:
A. x = 1/2y